Parametric study of glycerol and contaminants removal from biodiesel through solvent-aided crystallization - Ahmad, M.A. (Springer Science and Business Media Deutschland GmbH, 2021)
At present, biodiesel is known as an alternative fuel globally. It is also known that the purification of biodiesel before consumption is mandatory to comply with international standards. Commonly, purification using water washing generates a massive amount of wastewater with a high content of organic compounds that can harm the environment. Therefore, this study applied and tested a waterless method, i.e., the solvent-aided crystallization (SAC), to remove glycerol and other traces of impurities in the crude biodiesel. The parameters of coolant temperature, crystallization time, and stirring rate on the SAC system were investigated. It was discovered that with 14Â Â°C coolant temperature, 300 RPM and higher cooling time result in the highest percentage of FAME up to 99.54, which indicates that contaminants' presence is limited in the purified biodiesel. The use of 1-butanol as the solvent for crystallization process remarkably enhanced the separation and improved the higher biodiesel quality. Figure not available: see fulltext. Â© 2021, The Author(s).